Resibufogenin Targets the ATP1A1 Signaling Cascade to Induce G2/M Phase Arrest and Inhibit Invasion in Glioma - Zhang, Xun; Yao, Zhong; Xue, Zhiyi; Wang, Shuai; Liu, Xuemeng; Hu, Yaotian; Zhang, Yan; Wang, Jian; Li, Xingang; Chen, Anjing (Frontiers in Pharmacology, 2022)
Resibufogenin (RB) is one of the main active ingredients of the traditional Chinese medicine Chansu and has received much attention for its efficacy in cancer treatment. However, the anticancer effects and the underlying mechanisms of RB on glioblastoma (GBM) remain elusive. Here, we found that RB induced G2/M phase arrest and inhibited invasion in a primary GBM cell line, P3#GBM, and two GBM cell lines, U251 and A172. Subsequently, we demonstrated that RB‐induced G2/M phase arrest was through downregulation of CDC25C and upregulation of p21 which was caused by activation of MAPK/ERK pathway, and that RB inhibited GBM invasion by elevating intercellular Ca2+ to suppressing Src/FAK/Paxillin focal adhesion pathway. Intriguingly, we confirmed that upon RB binding to ATP1A1, Na+-K+-ATPase was activated as a receptor and then triggered the intracellular MAPK/ERK pathway and Ca2+-mediated Src/FAK/Paxillin focal adhesion pathway, which led to G2/M phase arrest and inhibited invasion of GBM cells. Taken together, our findings reveal the antitumor mechanism of RB by targeting ATP1A1 signaling cascade and two key signaling pathways and highlight the potential of RB as a new class of promising anticancer agent.